Development of engineering activities - Sadykova, Zhanna (Рroblems of engineering and professional education, 2023)
The article discusses the role of life, role and development of engineering activities, engineering work. Special attention was paid to the work of the engineering services with the owners of other professions, in particular inventors, designers, mathematicians and physicists.